The Influence of Regional Minimum Wages, Poor Population, Education Expenditures, and Health Expenditures on the Human Development Index in North Sumatra Province 2015-2021 - Dea Rahma Ardini; Antoni Sitorus (Proceedings of Bengkulu International Conference on Economics, Management, Business, and Accounting, 2023)
The objective of this study is to learn how the index development of humans in North Sumatra province in 2015–2021 was affected by the regional minimum wage, population poverty, shopping education, and shopping health. Panel data is used. In this analysis, index development is used as a variable, whereas regional minimum wage, population poverty, shopping education, and shopping health are variables. For do analysis, the E-Views 13 program was used for do analysis regression multiple. The study's findings show that variable regional minimum wages are positively and significantly correlated to index human development, whereas variable resident poverty is negatively and significantly correlated. Otherwise, no. There is a significant correlation between index development and variable shopping education and health. As a result, policy planning for sustainable development is a must.